Development of Hospital Pharmacy Practice in the Special Hospital for Addictive Disease: DEVELOPMENT OF HOSPITAL PHARMACY PRACTICE IN THE SPECIAL HOSPITAL FOR ADDICTIVE DISEASES - Zdravković, Nataša; Ristić, Jelena; Milošević Georgiev, Andrijana (Archives of Pharmacy, 2022)
The Special Hospital for Addiction Diseases (SBBZ) received the status of a secondary level health care institution and reference center for addiction diseases in 2007. The turning points in the development of the pharmacy service in SBBZ in the previous 60 years are presented, by applying the method of historical analysis for the period from 1958 until today. The dispensary for the treatment of alcoholics and the fight against alcoholism was founded in 1958 in Belgrade, and a hospital pharmacy within the Clinical Department for Alcoholism started operating there. For the next four decades, it grew into the Institute for Alcoholism (1968), the Institute for Alcoholism and Drug Addiction in 1973, and in 1980 changed its name to the Institute for Addiction Diseases. This health institution is part of the OOUR Clinic for Psychiatry and Neurology (1987), which was one of the working organizations of the Clinical Hospital Center "Dr Dragisa Misovic-Dedinje". The Institute for Addiction Diseases was founded in 1992, separated from the KBC and has been operating as the SBBZ since 2007 (1). With the independence of the hospital, the hospital pharmacy organizationally belonged to the laboratory and the hospital pharmaceutical activity was performed by only one pharmacist (2). It can be concluded that the transformation of the health institution had little impact on the work of the hospital pharmacy service because at all turning points there was always a pharmacist as the only professional, a holder of a job in a hospital pharmacy.